The role of local government in development with special reference to Middelburg - Evans, John David (My University, 1991)
During the 1980s considerable attention was focused on the need to develop institutions to draw populations into development efforts. Local government was the recipient of much of this attention. This study is concerned with the role of local government in development, and problems that are experienced in playing a developmental tole. In particular, it is concerned with international experience of local government as a development institution, and the relevance of that experience to SA. [No abstract provided. Information taken from introduction]
A discourse submitted to the Faculty of Architecture, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Development Planning. Johannesburg, 1991
Keywords: Local government--South Africa--Middelburg; Economic development--Case studies; Urban economics